The role of creativity in interpersonal communication in dance and movement therapy: narratives of practitioners - Gedvilaitė-Kordušienė, Margarita (Creativity Studies, 2022)
Based on the qualitative data, this paper aims to disclose the role of creativity in the therapeutic process from the perspective of dance and movement therapists in Lithuania. The literature on the concept of creativity and its interlinks with communication and the role of creativity is discussed. Based on the semi-structured interviews with dance and movement therapy practitioners, empirical findings reveal the role and meaning of creativity in the therapeutic process and discuss the elements of creativity in dance and movement therapy: game, spontaneity, and imagination. The practitioners of dance and movement therapy tend to conceptualize creativity broader than the classical definitions suggest. The role of creativity subjectively is interpreted as fundamental in the therapeutic process. It binds all other elements of the therapeutic process (such as movement, dance, and a therapeutic relationship); it is seen as a part of the communicative process between the therapist and a client. More specific identifications of the role of creativity foresee creativity as allowing to make a distance from emotionally painful situations and emotions.